RECOMMENDATIONS OF PILOTING A HELICOPTER AND FIGHTING AGAINST EXTERNAL GOODS OSCILLATIONS DURING THE CONDUCT OF URGENT AERIAL WORKS WITH EXTERNAL SUSPENSION - A. A. Lebedev (Научный вестник МГТУ ГА, 2017)
Сonsidered question of reducing oscillations of cargo on helicopter external sling to improve the safety and efficiency of flight operations during the conduct of urgent aerial works. Offered practical recommendations of piloting a helicopter and effective maneuvers to eliminate oscillations of cargo on external sling.